The Readability of Patient Education Materials Pertaining to Gastrointestinal Procedures - Mohammad S. Nawaz; Laura E. McDermott; Savanna Thor (Canadian Journal of Gastroenterology and Hepatology)
Introduction. Due to the ubiquity and ease of access of Internet, patients are able to access online health information more easily than ever. The American Medical Association recommends that patient education materials be targeted at or below the 6th grade level in order to accommodate a wider audience. In this study, we evaluate the difficulty of educational materials pertaining to common GI procedures; we analyze on the readability of online education materials for colonoscopy, flexible sigmoidoscopy, and esophagogastroduodenoscopy (EGD). Methods. Google search was performed using keywords of “colonoscopy,” “sigmoidoscopy,” and “EGD” with “patient information” at the end of each search term. The texts from a total of 18 studies, 6 for each of the procedures, were then saved. Each study was also subdivided into “Introduction,” “Preparation,” “Complications,” and if available, “Alternatives.” Furthermore, medical terminology that was properly explained, proper nouns, medication names, and other copyright text were removed in order to prevent inflation of the difficulty. Five validated readability tests were used to analyze each study and subsections: Coleman-Liau, New Dale-Chall, Flesch-Kincaid, Gunning Fog, SMOG. Results. Studies on colonoscopy, flexible sigmoidoscopy, and EGD had median readability grades of 9.7, 10.2, and 11.0, respectively. Analysis of the subsections revealed that the “Alternative” subsection was the most difficult to comprehend with a readability score of 11.4, whereas the “Introduction” subsection was the easiest to comprehend with a readability score of 9.5. Conclusion. Despite modifications to the studies that improved the readability scores, patient education materials were still significantly above the recommended 6th grade level across all websites. This study emphasizes that clear and simple language is warranted in order to create information that is suitable for most patients.